Linear and whorled nevoid hypermelanosis and Joubert syndrome: a novel association: A case report and literature review. (September 2019) - Fernandes, Carolina; Waddell, Andréanne; Jean, Sara-Élizabeth
This report discusses a case of linear and whorled nevoid hypermelanosis associated with cerebellar atrophy, ocular and developmental anomalies compatible with Joubert syndrome. Linear and whorled nevoid hypermelanosis is a rare disorder of skin pigmentation characterized by swirls and whorls of hyperpigmented macules in a reticulate pattern along Blaschko's lines. Neurologic, cardiac, skeletal and developmental anomalies have been reported. We present a case of linear and whorled nevoid hypermelanosis on an 18-year-old woman who also presented with cerebellar atrophy, jerk nystagmus, macrocephaly and developmental delay. Those symptoms were compatible with Joubert syndrome. A complete work-up failed to reveal other systemic or skeletal anomalies. No chromosomal alteration was found on karyotyping carried out on a skin specimen. Much remains to be known about linear and whorled nevoid hypermelanosis. It is generally a benign condition but association with various congenital anomalies have been reported. Proper work-up is advised in order to exclude congenital anomalies.